Knowledge and attitude of mothers with teenage daughters towards early marriage, its causes and consequences - Somayyeh Naghizadeh; Mojgan Mirghafourvand (Tehran University of Medical Sciences, 2022)
Background & Aim: Child marriage is a violation of human rights and children's rights. Since most of these marriages take place without the informed consent of children, and parents are the final decision makers. Therefore, the mothers' attitude towards the marriage of girls can have an undeniable effect on the early marriage of their daughters. The aim of the present study was to determine the knowledge and attitude of mothers with teenage daughters towards early marriage, its causes and consequences. Methods & Materials: This descriptive-analytical, cross-sectional study was conducted on 270 mothers with teenage daughters in Tabriz in 2020-2021. Data were collected using a researcher-made questionnaire, and were analyzed using descriptive statistics, one-way analysis of variance, Chi-square test and Fisher's exact test through the SPSS software version 21. Results: More than half (55.2%) of the mothers had a good level of knowledge about early marriage. The majority of mothers (87.0%) were against marriage before the age of 18. There was a statistically significant relationship between mothers' knowledge and attitude towards early marriage (P<0.001). The emotional, social, intellectual and economic maturity of girls were the most important reasons for the decrease in early marriage, and one of the most important reasons for the increase in early marriage was not reaching intellectual-psychological maturity. The most important consequence of early marriage from the mothers' points of view was the high possibility of family involvement in married life and decision-making. Conclusion: Despite the negative attitude of mothers towards early marriage, nearly half of them had poor and moderate levels of knowledge regarding early marriage. Therefore, raising the level of knowledge of mothers with teenage daughters about the consequences of early marriage, creating a culture to correct social misconceptions, passing appropriate laws to prevent child marriage, can reduce the severity of this harm.